Tata Kelola dan Kedinamisan Lingkungan sebagai Determinan Kinerja Startup: Peran Moderasi Keunggulan Kompetitif - Yuha Nadhirah Qintharah (Jurnal Akuntansi dan Bisnis, 2025)
This study aims to analyze the influence of governance and environmental dynamism on startup performance, as well as to examine the moderating role of competitive advantage. The research is based on primary data collected through the distribution of questionnaires. The respondents consist of startups from across Indonesia, with CEOs and CFOs from 371 startups. This study also develops a new measurement to assess the dimension of environmental dynamism in a more contextualized for the startup sector. The results indicate that governance and environmental dynamism have a positive and significant impact on startup performance. Findings reveal that competitive advantage significantly moderates the relationship between environmental dynamism and performance, strengthening its positive effect. This study confirms that competitive advantage plays an effective role as a moderating variable.